2007
DOI: 10.1080/09583150701527094
|View full text |Cite
|
Sign up to set email alerts
|

Trichodermaspp. as elicitors of wheat plant defense responses againstSeptoria tritici

Abstract: Leaf blotch of wheat is a widespread and highly active disease that affects wheat production. In addition to the use of chemicals and proper cultivation methods, microbial antagonists are used to control plant pathogens. Trichoderma spp. stimulate a systemic induced response in plants. Therefore, the efficacy of Trichoderma spp. against wheat leaf blotch was evaluated under greenhouse conditions. The susceptible plants were sprayed with Septoria tritici conidiospores. In order to select an efficient method of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
18

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 45 publications
(50 reference statements)
3
27
0
18
Order By: Relevance
“…The isolates T5 (Trichoderma harzianum) and T6 (T. koningii) were originally obtained from wheat phylloplane and parasited sclerotia from Sclerotinia sclerotiorum respectively. T. harzianum has previously been reported as a biocontrol agent in the aerial environment on different crops including other wheat diseases (Cordo et al 2007;Elad 2000;Hermosa et al 2000;Mónaco et al 2004;Perello et al 1997Perello et al , 2003. Previous assays in Argentina have demonstrated that some T. harzianum isolates were capable of suppressing growth and mycelial development of PTR and the severity of disease on wheat plants (Perelló et al 2003(Perelló et al , 2006.…”
Section: Discussionmentioning
confidence: 97%
“…The isolates T5 (Trichoderma harzianum) and T6 (T. koningii) were originally obtained from wheat phylloplane and parasited sclerotia from Sclerotinia sclerotiorum respectively. T. harzianum has previously been reported as a biocontrol agent in the aerial environment on different crops including other wheat diseases (Cordo et al 2007;Elad 2000;Hermosa et al 2000;Mónaco et al 2004;Perello et al 1997Perello et al , 2003. Previous assays in Argentina have demonstrated that some T. harzianum isolates were capable of suppressing growth and mycelial development of PTR and the severity of disease on wheat plants (Perelló et al 2003(Perelló et al , 2006.…”
Section: Discussionmentioning
confidence: 97%
“…More recently, a maize protein ZmGLP1 with sequence similarity to the barley GLP with AGPPase activity has also been reported (Fan et al, 2005). Additionally, a GLP which inhibits serine protease activity has been reported in the wheat apoplast and suggested to be part of a defense system against insect and bacterial proteases (Segarra et al, 2003;Cordo et al, 2007). Such biotic responses are discussed below.…”
Section: Biochemical Propertiesmentioning
confidence: 90%
“…En concordancia con Mukhopadhyay et al, (1992) un método efectivo para incorporar el antagonista es recubrir las semillas. Cordo et al, (2007) establecieron que la técnica de recubrimiento de semillas es más efectiva contra la mancha foliar del trigo que la técnica de asperjado foliar. En el recubrimiento de semilla los propágulos de los agentes de biocontrol germinan en la superficie de esta y colonizan las raíces de las plántulas y la rizosfera rápidamente (Kumar et al, 2009).…”
Section: Discussionunclassified
“…Cepa de Trichoderma harzianum La cepa de Trichoderma harzianum Th5cc, se encuentra conservada en el Banco Micológico que funciona en Centro de Investigaciones de Fitopatología (CIDEFI-UNLP) perteneciente a la Facultad de Ciencias Agrarias y Forestales de la Universidad Nacional de La Plata (Stocco et al, 2011). Esta cepa fue aislada del filoplano de trigo y utilizada como antagonista de Zymoseptoria tritici por Cordo et al, (2007). Se identificó molecularmente siguiendo la técnica descripta por Stocco et al, (2016).y fue depositada en la base de datos del European Molecular Biology Laboratory (EMBL) bajo el número de accesión LN869401.…”
Section: Materiales Y Métodosunclassified
See 1 more Smart Citation